2001
DOI: 10.1038/35070129
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the APC tumour suppressor gene cause chromosomal instability

Abstract: Two forms of genetic instability have been described in colorectal cancer: microsatellite instability and chromosomal instability. Microsatellite instability results from mutations in mismatch repair genes; chromosomal instability is the hallmark of many colorectal cancers, although it is not completely understood at the molecular level. As truncations of the Adenomatous Polyposis Coli (APC) gene are found in most colorectal tumours, we thought that mutations in APC might be responsible for chromosomal instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
474
4
19

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 670 publications
(529 citation statements)
references
References 35 publications
26
474
4
19
Order By: Relevance
“…It has been reported that APC binds to the kinetochore, and that its truncation mutations cause polyploidy (Fodde et al, 2001;Kaplan et al, 2001). However, APC is a multifunctional protein and it plays a key role also in the canonical Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that APC binds to the kinetochore, and that its truncation mutations cause polyploidy (Fodde et al, 2001;Kaplan et al, 2001). However, APC is a multifunctional protein and it plays a key role also in the canonical Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between APC and b-catenin suggested that expression of the stable b-catenin in ES cells might cause CIN indirectly through interfering with the kinetochore binding of APC (Fodde et al, 2001;Kaplan et al, 2001). To exclude such a possibility, we chose cells that lack both wild-type APC alleles but show little CIN, that is, DLD-1 cells that are MIN cell line with near-diploid chromosome content, and show minimal CIN (Aoki et al, 2003;Stewenius et al, 2005).…”
Section: Es Cells With High Abi Produce New Chromosomal Aberrationsmentioning
confidence: 99%
See 3 more Smart Citations